坐骨神経損傷マウスから摘出した後根神経節神経細胞の突起伸長促進にはマクロファージ由来HMGB1が関与する - 坪田, 真帆; 西堀, 正洋; 関口, 富美子; 中武, ゆい; 川畑, 篤史 (日本薬理学会年会要旨集, 2021)
A nuclear protein, high mobility group box 1 (HMGB1), when extracellularly released, enhances neuritogenesis via activation of the receptor for advanced glycation end-products (RAGE). Given evidence that preconditioning peripheral nerve injury (PPNI) enhances axonal regeneration of isolated dorsal root ganglion (DRG) neurons, we examined possible involvement of HMGB1 in the underlying mechanisms. HMGB1 in a reduced form significantly increased neurite outgrowth in DRG neurons isolated from naïve mice, an effect blocked by a RAGE antagonist. DRG neurons isolated from the mice 6 days after subjected to PPNI, i.e. sciatic nerve crush, exhibited significantly increased neurite outgrowth, compared with the control mice, being resistant to in vitro exposure to an anti-HMGB1-neutralizing antibody (nAb). Meanwhile, daily i.p. injection of nAb for 5 days after PPNI blocked the increased neuritogenesis in the isolated DRG neurons. Repetitive i.p. injection of minocycline, an inhibitor of microglia/macrophage (Mφ), or ethyl pyruvate, known to suppress HMGB1 release from Mφ, also blocked the PPNI-accelerated neuritogenesis in DRG neurons. The number of Mφ markedly increased in the sciatic nerves after PPNI. The data suggest that Mφ-derived HMGB1 contributes to axonal elongation and/or regeneration of DRG neurons after PPNI in mice.